Mandarin version of the Leeds Dyspepsia Questionnaire: a valid instrument for assessing symptoms in Asians - Leow, Hwong Ruey; Ching, Siew Mooi; Ramanujam, Sujarita; Yap, Choong Foong; Chia, Yook Chin; Ho, Shiaw-Hooi; Sithambaram, Suresh; Tan, Huck Joo; Goh, Khean Lee; Mahadeva, Sanjiv (Wiley-Blackwell Publishing, 2014)
Objective To develop and validate a Mandarin version of the Leeds Dyspepsia Questionnaire (M-LDQ) in Asian patients with dyspepsia. Methods The M-LDQ was developed according to standardized methods. The validity, internal consistency, test–retest reliability and responsiveness of the instrument were evaluated in both primary and secondary care patients. Results A total of 184 patients (mean age 54.0 ± 15.8 years, of whom 59% were women and 72.3% of whom had at least secondary level education) were recruited between August 2012 and March 2013, from both primary (n = 100) and secondary care clinics (n = 84). Both the internal consistency of all components of the M-LDQ (Cronbach's α 0.79) and test–retest reliability (Spearman's correlation coefficient 0.78) were good. The M-LDQ was valid in diagnosing dyspepsia in primary care (area under the receiver operating characteristics curve 0.84) and was able to discriminate between secondary and primary care patients (median cumulative LDQ score 13.0 vs 3.0, P < 0.0001). Among eight patients with organic dyspepsia, the median M-LDQ score reduced significantly from 21.0 (pretreatment) to 9.5 (4 weeks post-treatment) (P < 0.0001). Conclusion The M-LDQ is a valid and responsive instrument for assessing ethnic Chinese adults with dyspepsia.